National Productivity Award Model to Accelerating Sustainable Practices in the Mining Industry - Behzad Mohammadian; Mahsa Pishdar; Hassan Zarei Matin; Adel Pourghader Chobar (Sustainable Earth Trends)
The mining industry significantly impacts national economies. However, there is a lack of industry-specific productivity frameworks that support sustainable development in this sector. This study aims to fill that gap by creating a national productivity award model tailored to Iran's mining industry. Using a methodological synthesis, the research begins with an analysis of key success factors and a comparison of national and international productivity evaluation systems.  The resulting framework comprises three main components of productivity drivers with a maximum obtainable score of 200 points, focusing on leadership, culture, strategy, and governance. Productivity enablers with a maximum score of 350 points as the second component focus on critical resources and capabilities such as staff management to facilitate productivity. The last component is the consequences of productivity with a maximum obtainable score of 450 points, paying attention to the assessment of both perceptual and operational achievements. These 3 main components are built on ten core values, such as intelligent production, systems thinking, sustainable development, and leadership.  This model not only fosters continuous improvement but also addresses challenges with minimal resistance, enabling sustainable transformation in the mining sector. Measuring drivers like workforce efficiency, skill level, and technology use can reveal specific gaps where productivity is hindered. Strengthening workforce competencies through continuous training and safety protocols. The consequences of productivity, boosting long-term profitability, and environmental compliance could be mentioned. Adopting sustainable mining practices not only aligns with regulatory compliance but can reduce waste and enhance corporate reputation.